(untitled) (Indian Journal of Arid Horticulture, 2025)
Watermelon [Citrullus lanatus (Thunb) Mansf.] is one of the most widely cultivated crop in the world. China is the leading country in production of watermelon followed by Turkey, United States, Iran and Republic of Korea (Huh et al., 2008). This crop is also known as Tarbooj, Kalinda and Mateera in India. It accounts for 6.8% of the world area devoted to vegetable production (Goreta et al., 2005). Farrukhabadi, Moradabadi, Faizabadi of Uttar Pradesh and Mateera of Rajasthan are an important landraces of watermelon grown by farmers using their own saved seeds. It has sufficient variability for high productivity, quality, appearance traits such as shape, size, colour and is able to withstand damage from biotic and abiotic factors (Wehner et al., 2001). It is subjected to attack of a number of fungal, bacterial and viral diseases, which inflict heavy damage on yield of the crop every year. Among the fungal diseases, Alternaria blight is an important disease in Rajasthan and other watermelon growing states of India. This disease needs regular monitoring for evolving effective control measures. Keeping the above facts in mind, a survey was conducted to record the status of Alternaria blight in four districts of Rajasthan at farmer’s fields and the results are presented in Table 1 and Fig. 1.